Two diverse carriers are better than one: A case study in α‐particle therapy for prostate specific membrane antigen‐expressing prostate cancers. Issue 2 (17th November 2021) - Salerno, Dominick; Howe, Alaina; Bhatavdekar, Omkar; Josefsson, Anders; Pacheco‐Torres, Jesus; Bhujwalla, Zaver M.; Gabrielson, Kathleen L.; Sofou, Stavroula
Abstract: Partial and/or heterogeneous irradiation of established (i.e., large, vascularized) tumors by α‐particles that exhibit only a 4–5 cell‐diameter range in tissue, limits the therapeutic effect, since regions not being hit by the high energy α‐particles are likely not to be killed. This study aims to mechanistically understand a delivery strategy to uniformly distribute α‐particles within established solid tumors by simultaneously delivering the same α‐particle emitter by two diverse carriers, each killing a different region of the tumor: (1) the cancer‐agnostic, but also tumor‐responsive, liposomes engineered to best irradiate tumor regions far from the vasculature, and (2) a separately administered, antibody, targeting any cancer‐cell's surface marker, to best irradiate the tumor perivascular regions. We demonstrate that on a prostate specific membrane antigen (PSMA)‐expressing prostate cancer xenograft mouse model, for the same total injected radioactivity of the α‐particle emitter Actinium‐225, any radioactivity split ratio between the two carriers resulted in better tumor growth inhibition compared to the tumor inhibition when the total radioactivity was delivered by any of the two carriers alone. This finding was due to more uniform tumor irradiation for the same total injected radioactivity. The killing efficacy was improved even though the tumor‐absorbed dose delivered by the combined carriers was lower than the tumor‐absorbed dose delivered by the antibody alone. Studies on spheroids with different receptor‐expression, used as surrogates of the tumors' avascular regions, demonstrated that our delivery strategy is valid even for as low as 1+ (ImmunoHistoChemistry score) PSMA‐levels. The findings presented herein may hold clinical promise for those established tumors not being effectively eradicated by current α‐particle radiotherapies.